New Horizons for Newcomer Organizational Socialization: A Review, Meta-Analysis, and Future Research Directions - Bauer, Talya N.; Erdogan, Berrin; Ellis, Allison M.; Truxillo, Donald M.; Brady, Grant M.; Bodner, Todd (Journal of Management, 2025)
The effective socialization of newcomers into organizations is critical for employee and organizational success. As such, ensuring successful onboarding has become even more pivotal for newcomer adjustment, performance, and retention. The literature has seen significant growth and incorporated new theoretical perspectives, such as resource-based approaches since the most recent comprehensive meta-analytic review of the literature. Therefore, we extended earlier reviews by presenting an updated model of the socialization process, reviewing the literature, and examining this updated model via meta-analysis. In all, we identified 256 studies that met our meta-analytic inclusion criteria, and 183 with sufficient k across construct categories were included in our meta-analysis. At the correlational level, we analyzed antecedents to proximal adjustment indicators and proximal adjustment to distal outcomes. We examined a potential moderator, whether the study took place in a horizontal-individualistic (HI) versus vertical-collectivistic (VC) culture. Last, we analyzed a path model to identify unique relationships between specific antecedents (age, full-time work experience, organizational tenure, proactive personality, information seeking, organizational tactics, insider mentoring/supporting), proximal adjustment indicators (social acceptance, role clarity, task mastery, perceived fit), and distal outcomes (job satisfaction, organizational commitment, turnover intentions, other-rated performance, and well-being). Our analyses uncover the role of proactive personality and proactive newcomer behaviors in newcomer adjustment and the importance of social acceptance for newcomers. They also identify perceptions of fit as an important but relatively under-examined adjustment indicator and newcomer well-being as an additional socialization outcome. We develop future directions for socialization theory and research methods.